Sellar Region Atypical Teratoid/Rhabdoid Tumors (ATRT) in Adults Display DNA Methylation Profiles of the ATRT-MYC Subgroup - Johann, Pascal D.; Bens, Susanne; Oyen, Florian; Wagener, Rabea; Giannini, Caterina; Perry, Arie; Raisanen, Jack M.; Reis, Gerald F.; Nobusawa, Sumihito; Arita, Kazunori; Felsberg, Joerg; Reifenberger, Guido; et al. (American Journal of Surgical Pathology, 2018)
Atypical teratoid/rhabdoid tumor (ATRT) is a highly malignant brain tumor predominantly encountered in infants. Mutations of the SMARCB1 gene are the characteristic genetic lesion. A small group of ATRT stands out clinically, because these tumors are located in the sellar region of adults. To investigate if sellar region ATRT in adults represents a molecular distinct entity, we characterized molecular alterations in 7 sellar region ATRTs in adults as compared with 150 pediatric ATRTs and 47 pituitary adenomas using SMARCB1 sequencing, multiplex ligation-dependent probe amplification and fluorescence in situ hybridization as well as DNA methylation profiling. The median age of the 6 female and 1 male patients was 56 years. On histopathologic examination, all tumors were malignant rhabdoid tumors showing loss of SMARCB1/INI1 protein expression. Two cases displayed compound heterozygous SMARCB1 point mutations, 3 cases showed heterozygous SMARCB1 deletions with point mutations of the other allele and 1 case a homozygous SMARCB1 deletion; in 1 case, underlying SMARCB1 alterations could not be identified. On unsupervised hierarchical cluster analysis of DNA methylation profiles, sellar region ATRTs did not form a distinct group, but clustered with ATRT-MYC, 1 of 3 recently described molecular subgroups of ATRT. On analysis of DNA methylation array intensity data, only 1 sellar region ATRT showed characteristic features of pediatric ATRT-MYC, that is, major copy number losses affecting the SMARCB1 region. In conclusion, these results suggest that sellar region ATRTs in adults form a clinically distinct entity with a different mutational spectrum, but epigenetic similarities with pediatric ATRTs of the ATRT-MYC subgroup.
EVALuna2:34888